Production of non-mosaic genome edited porcine embryos by injection of CRISPR/Cas9 into germinal vesicle oocytes. (20th July 2019) - Su, Xiaohu; Chen, Wei; Cai, Qingqing; Liang, Puping; Chen, Yaosheng; Cong, Peiqing; Huang, Junjiu
Abstract: Genetically modified pigs represent a great promise for generating models of human diseases and producing new breeds. Generation of genetically edited pigs using somatic cell nuclear transfer (SCNT) or zygote cytoplasmic microinjection is a tedious process due to the low developmental rate or mosaicism of the founder (F0). Herein, we developed a method termed germinal vesicle oocyte gene editing (GVGE) to produce non-mosaic porcine embryos by editing maternal alleles during the GV to MⅡ transition. Injection of Cas9 mRNA and X-linked Dmd gene-specific gRNA into GV oocytes did not affect their developmental potential. The MⅡ oocytes edited during in vitro maturation (IVM) could develop into blastocysts after parthenogenetic activation (PA) or in vitro fertilization (IVF). Genotyping results indicated that the maternal gene X-linked Dmd could be efficiently edited during oocyte maturation. Up to 81.3% of the edited IVF embryos were non-mosaic Dmd gene mutant embryos. In conclusion, GVGE might be a valuable method for the generation of non-mosaic maternal allele edited F0 embryos in a short simple step.